Ad-layers enhance graphene's performance. Issue 114 (3rd November 2015) - Chen, Ting-Wei; Hsieh, Ya-Ping; Hofmann, Mario
Abstract : Graphene's performance as transparent conductor can be significantly enhanced by discontinuous ad-layers on top of a complete graphene sheet by providing highly efficient parallel pathways for carrier transport. Abstract : Graphene, a monoatomic sheet of graphite, could find application as a transparent conducting film (TCF) in solar cells and electronic devices. Currently available graphene, however, does not meet industry requirements in conductivity for these uses. We here demonstrate that ad-layers, discontinuous graphene islands on top of a complete graphene layer, can significantly enhance graphene's TCF-performance. Two routes were employed to produce controllable densities of ad-layers. Electropolishing pretreatment of the catalyst was found to affect the ad-layer nucleation. Alternatively, variation of the growth parameters was employed to influence the density of ad-layer dimensions. By analyzing the coverage-dependent carrier transport, we identified a continuous enhancement even by small ad-layers. This surprising behavior was quantitatively explained by a high conductivity parallel current path through the ad-layers. The resulting ad-layer-covered graphene exhibits a high and tunable performance as a transparent conductor.